Improvement of Flexural and Shear Strength of RC Beam Reinforced by Glass Fiber-Reinforced Polyurea (GFRPU) - Song, Jun-Hyeok; Eun, Hee-Chang (Civil Engineering Journal, 2021)
The Glass Fiber-Reinforced Polyurea (GFRPU) which is the composite by the elastic polyurea and milled glass fiber have the mechanical characteristics to enhance tensile strength as well as ductility. It must be reinforcement materials in repair and retrofit applications for strengthening structural capacity and has a merit of simple construction of spray coating to prevent the debonding from concrete surfaces unlike the existing strengthening methods such as Fiber-reinforced polymer (FRP) or steel plate. This work compares the improvement degree in load-carrying capacity as well as flexural ductility of RC beam reinforced externally by polyurea or GFRPU. Seven specimens of four reinforced concrete (RC) beams for evaluating flexure-resisting capacity and three beams for shear-strengthening capacity are tested. The mechanical behavior and characteristics of the specimens reinforced by local and global reinforcement method classified according to strengthened area are compared. It is shown that the polyurea- or GFRPU- reinforcement leads to the enhancement in the load-resisting capacity up to 8~11% and flexural ductility within the range of 8.41~13.9 times of the non-reinforced beam. And the global reinforcement method has more improvement in the shear- and flexure-resisting capacity than the local method. It is also observed that the GFRPU can be more effectively utilized in enhancing the structural shear-resisting capacity than the flexure-carrying capacity.Â Doi: 10.28991/cej-2021-03091662 Full Text: PDF